3(3x-5)+4-2x=23

Simple and best practice solution for 3(3x-5)+4-2x=23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(3x-5)+4-2x=23 equation:


Simplifying
3(3x + -5) + 4 + -2x = 23

Reorder the terms:
3(-5 + 3x) + 4 + -2x = 23
(-5 * 3 + 3x * 3) + 4 + -2x = 23
(-15 + 9x) + 4 + -2x = 23

Reorder the terms:
-15 + 4 + 9x + -2x = 23

Combine like terms: -15 + 4 = -11
-11 + 9x + -2x = 23

Combine like terms: 9x + -2x = 7x
-11 + 7x = 23

Solving
-11 + 7x = 23

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '11' to each side of the equation.
-11 + 11 + 7x = 23 + 11

Combine like terms: -11 + 11 = 0
0 + 7x = 23 + 11
7x = 23 + 11

Combine like terms: 23 + 11 = 34
7x = 34

Divide each side by '7'.
x = 4.857142857

Simplifying
x = 4.857142857

See similar equations:

| 5-4(y+2)= | | W^2+13=0 | | =0.8Y-(100+0.15Y)-0.15Y | | 20-20d-4=-15d-19 | | 10x+3y+6z-5x+5z-4y= | | 135.32=2.74h+72.07 | | 3.14(10*65)= | | 1-7p=-15-8p | | -11u+19=-9-15u | | 49x^2-5=28 | | 2x+x=52-x | | -7x-15=14-12x+16 | | 6.5d+7(-1.3d-3)= | | -12u-16=19-17u | | 4(3p-4)-3(4p-5)= | | x^5+15x^3+54x=0 | | x+20=-16 | | 2x+18+2x-13+x=180 | | -5=r/4-3 | | -12h+3g=-4h-17 | | -5(4x-3)+9x=-7 | | -18=-20a | | 5x+1/6+2x+1/3=2 | | -(3y-2)= | | 5x+10+6x-4=180 | | 4(2a+3b)-3(a+2b)= | | 4squared+x=w | | 70+[(-117)+(-72)]= | | 1/2+11/3= | | 1/2+1*1/3= | | 20X^3-180x^2=0 | | 7t+8(5-3t)= |

Equations solver categories